Observed difficulties during implementation of quality management systems in Brazilian manufacturing companies - Rosley Anholon and Izabela Simon Rampasso and Robert Eduardo Cooper Ordonez and Dirceu da Silva and Osvaldo Luiz Goncalves Quelhas and Walter Leal Filho (Journal of Manufacturing Technology Management, 2018)
Purpose The purpose of this paper is to analyze the difficulties observed during implementation of quality management systems (QMSs) in Brazilian manufacturing companies. Design/methodology/approach The methodological strategy used was a literature review, a panel of experts and a survey. Through the literature review, 15 difficulties associated with the implementation of QMS were raised; these were organized into latent variables by specialists in the subject and served as the basis for a survey. In total, 123 professionals working with quality management in manufacturing companies participated in the research and the data collected were analyzed by means of second-order confirmatory factorial analysis. Findings The results allowed the validation of the 15 difficulties observed in the literature, and it was evidenced that these difficulties are structured in four latent variables as follows: difficulties associated with employees; difficulties associated with QMS structuration; difficulties associated with integration; and difficulties resulting from the planning. Research limitations/implications The main limitation of this research is the sample size, because 123 professionals that work with quality management in manufacturing companies participated in the research. It should be noted, however, that all parameters evaluated through the second-order confirmatory factorial analysis were validated. Practical implications The findings have great value for both quality management professionals, who may use those findings to guide the pre-implementation phase of a QMS, and researchers, who may use those findings as a foundation for future studies, in the development of models or tools related to QMS implementation. Originality/value No other paper was found on the scientific basis with the same focus for Brazilian manufacturing companies, thus demonstrating originality. The value of the research lies in the fact that the results presented here, statistically validated, may be used by other researchers and market professionals.